Turnpike properties of discrete dispersive dynamical systems with a Lyapunov function. (3rd April 2022) - Zaslavski, Alexander J.
Abstract: In this paper, we study turnpike properties for discrete disperse dynamical systems generated by set-valued mappings which were introduced by A. M. Rubinov in 1980.